2008
DOI: 10.1080/14017430701819105
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of symptomatic, unruptured abdominal aortic aneurysms after endovascular repair with the Zenith stent-graft system

Abstract: These preliminary results suggest that endovascular repair of symptomatic, unruptured AAA is feasible and can be associated with a favourable outcome despite a very high operative risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…35,10,13,14,18 Our incidence is near the low end of the reported spectrum, similar to the 2008 report of Nevala et al 2 who reported a 6% frequency of Sx-AAA. It is unclear if these more contemporary cohorts have a lower frequency of Sx-AAAs based on increased surveillance or elective repair, or if this is related to other, unknown factors.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…35,10,13,14,18 Our incidence is near the low end of the reported spectrum, similar to the 2008 report of Nevala et al 2 who reported a 6% frequency of Sx-AAA. It is unclear if these more contemporary cohorts have a lower frequency of Sx-AAAs based on increased surveillance or elective repair, or if this is related to other, unknown factors.…”
Section: Discussionsupporting
confidence: 88%
“…Such AAAs are termed symptomatic and represent 5.5% to 22% of all AAAs that require operation in previously reported surgical series. 2–8 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevala and colleagues reported approximately 30% of the patient who underwent EVAR with the Zenith stentgraft required reintervention. 10) The authors focused on type II endoleak following Zenith stentgraft placement in another report, in which type II endoleak occurred in 22% of the patients, and reintervention was required in 6.4% of the entire cohort. They performed translumber or transarterial embolization with success rate of approximately 38%, and concluded the results of percutaneous reinterventions for type II endoleak were unsatisfactory.…”
Section: Methodsmentioning
confidence: 99%